PENGARUH PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN BEBERAPA VARIETAS JAGUNG MANIS DI LAHAN TSUNAMI - Mardhiah Hayati; Erita Hayati; Denni Denni (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
The study was aimed at determining responses of several sweet corn varieties to organic and inorganic fertilizers on tsunami affected land and knowing interactions between both factors on growth and yield of sweet corn. The experiment was conducted in Village of Lampuuk, Lhoknga, District of Aceh Besar, from January 7 to March 19, 2008. This research was conducted using a randomized complete block design (RCBD), 3 x 3 with 3 replications. There were two factors studied, namely fertilizations, consisting of 3 levels: 100% organic fertilizer, 50% organic fertilizer + 50% inorganic fertilizers and 100% inorganic fertilizers. The second factor was varieties, consisting of 3 levels: Sweet Boy, Hawaiian Sweet Corn Hybrid F1 and Super Bee. The results showed that fertilization significantly affected ear weight with and without cornhusk, but did not affect diameter of ear and seed rows per ear. The highest result was found at a treatment of 50% organic fertilizer + 50% inorganic fertilizers, but was not significantly different from 100% organic fertilizer. Varieties showed no significant effects on all variables observed. There were significant interactions between fertilizations and varieties on plant height at age 42 and 63 day after planting (DAP), leaf length at age 21, 42, and 63 DAP, and root fresh weight at age 21 DAP. The best plant growth was found at a combination of Sweet Boy and 50% organic fertilizer + 50% inorganic fertilizer.